Tools to measure the technological capabilities of the aerospace industry - Acela Castillón-Barraza; Alvaro González-Angeles; Fernando Lara-Chavez; Ismael Mendoza-Mu\~noz (Journal of Industrial Engineering and Management (JIEM), 2018)
Purpose: The following article describes steps along with a mathematical model to determine the technological capability of the aerospace industry of Mexicali in the area of design (ICTD) and manufacturing (ICTM). Design/methodology/approach: This model was performed by weighted variables using factor analysis to identify technological capacities of Small and medium-sized enterprises (SMEs) and compare them with those that must be accomplish to become suppliers for transnational industry (TNCs). Findings: The results suggest that SMEs must realize a comparative table QFD of their current capabilities and the requirements established by transnational corporations, to create a strategic plan that includes; certifications (AS 9000, NAP CAP, Belts, ISO, Six Sigma), software acquisition and updated equipment necessary for reducing the technological gap. Additionally, it is recommended the integration of clusters of enterprises SMEs for the strengthening of technological capacities. Originality/value: Up to we know, there is not similar model for measuring technological capabilities of aerospace industry.
Keywords: 650; SMEs; technological capabilities index; technology transfer; diagnostics; supplier development